Long‐term colorectal cancer incidence and mortality after adenoma removal in women and men. Issue 4 (30th October 2021) - Jodal, Henriette C.; Klotz, Dagmar; Herfindal, Magnhild; Barua, Ishita; Tag, Petter; Helsingen, Lise M.; Refsum, Erle; Holme, Øyvind; Adami, Hans‐Olov; Bretthauer, Michael; Kalager, Mette; Løberg, Magnus
Summary: Background: Women and men with colorectal adenomas are at increased risk of colorectal cancer and colonoscopic surveillance is recommended. However, the long‐term cancer risk remains unknown. Aims: To investigate colorectal cancer incidence and mortality after adenoma removal in women and men Methods: We identified all individuals who had adenomas removed in Norway from 1993 to 2007, with follow‐up through 2018. We calculated standardized incidence ratios (SIR) and incidence‐based mortality ratios (SMR) with 95% confidence intervals (CI) for colorectal cancer in women and men using the female and male population for comparison. We defined high‐risk adenomas as ≥2 adenomas, villous component, or high‐grade dysplasia. Results: The cohort comprised 40 293 individuals. During median follow‐up of 13.0 years, 1079 women (5.5%) and 866 men (4.2%) developed colorectal cancer; 328 women (1.7%) and 275 men (1.3%) died of colorectal cancer. Colorectal cancer incidence was more increased in women (SIR 1.64, 95% CI 1.54‐1.74) than in men (SIR 1.12, 95% CI 1.05‐1.19). Colorectal cancer mortality was increased in women (SMR 1.13, 95% CI 1.02‐1.26) and reduced in men (SMR 0.79, 95% CI 0.71‐0.89). Women with high‐risk adenomas had an increased risk of colorectal cancer death (SMR 1.37, 95% CI 1.19‐1.57); women with low‐risk adenomas (SMR 0.90, 95% CI 0.76‐1.07) and men with high‐risk adenomas had a similar risk (SMR 0.89, 95% CI 0.76‐1.04), while men with low‐risk adenomas had reduced risk (SMR 0.70, 95% CI 0.59‐0.84). Conclusions: After adenoma removal, women had an increased risk of colorectal cancer death, while men had reduced risk, compared to the general female and male populations. Sex‐specific surveillance recommendations after adenoma removal should be considered. Abstract : The risk of colorectal cancer incidence and mortality after adenoma removel was investigated in a cohort of 40 293 individuals who have had adenomas removed, with a median of 13.0 years of follow‐up. We found that the risk of colorectal cancer mortality after adenoma removal was increased in women, but reduced in men, compared to the general female and male populations. Sex‐specific surveillance recommendations after adenoma removal should be considered.